Trajectory planning for low cost quadrotor through an educational software (Revista Cientifica Ingenio Magno, 2018)
This article is presented as a consultation paper for undergraduate and postgraduate students in the engineering airfield, which requires an implementation of fast and efficient control of an aerial robot. It aims tat presenting the design and implementation of a trajectory planner for a low cost quadrotor used as a research object. In addition, you will find that a conceptualization of the necessary mathematical analysis is made corresponding to the quadrotor-type multirotors, the control strategy, the calculation of the point-to-point trajectory planner with a trapezoidal velocity profile built in educational software and later the analysis of the results obtained in practice through an experimental validation of the same in the platform Ar.drone2 of the company Parrot vs the simulation carried out. These results will allow determining the effectiveness of the trajectory planner according to the computed coordinates XYZ, for this investigation it was not interacted with the orientation of the aerial robot, that is, there is no control over the rotation with respect to the Z-axis.
Keywords: Ar.drone; coordinates; educational software; Quadrotor; trajectory; speed